Mosaics of the nowadays Ukraine as a resurrection of Kyiv Rus traditions - Kotsuibanska, Olga; Levitska, Nadiia (My University, 2017)
The abstract is dedicated to the history of contemporary art – to the creation of the “Golden Gate” metro station.
Keywords: department of humanitarian disciplines; кафедра гуманітарних дисциплін; art; мистецтво; ceramic; керамика; кераміка; independent Ukraine; незалежна Україна